Moderate exercise in hypoxia induces a greater arterial desaturation in trained than untrained men - Woorons, X.; Mollard, P.; Pichon, A.; Lamberto, C.; Duvallet, A.; Richalet, J. P. (Scandinavian Journal of Medicine & Science in Sports, 2007)
During moderate exercise breathing a low inspired O2 fraction (FIO2), arterial O2 desaturation may depend on the fitness level. Seven trained (TM) and seven untrained men (UTM) cycled in normoxia and in hypoxia (FIO2=0.187, 0.173, 0.154, 0.13 and 0.117). We compared TM and UTM at submaximal intensities below the ventilatory threshold. Ventilatory variables were monitored and arterial oxygen saturation was measured by pulse oximetry. O2 saturation was not different between groups at sea level. In hypoxia, O2 saturation was lower in TM than in UTM at FIO2=0.154 (87.3 ± 2.9% vs 90.4 ± 1.5% at 90 W) and below. Both the ventilatory-equivalent and the end-tidal O2 pressure were lower in TM at sea level and at every FIO2, with the differences between TM and UTM becoming apparent at lower exercise intensity and increasing in magnitude as the severity of hypoxia increased. O2 saturation was correlated with the ventilatory parameters at every FIO2 and the correlations were stronger in severe hypoxia. These results demonstrate that a moderate exercise carried out in hypoxia, contrary to normoxic conditions, can lead to a greater arterial desaturation in TM compared with UTM. This phenomenon could be partly attributed to a relative hypoventilation in trained subjects.